IMPLEMENTATION OF THE PROVISION OF SOUND LETTERS IN THE GENERAL ELECTION OF 2019 IN RIAU PROVINCE BASED ON LAW NUMBER 7 OF 2017 CONCERNING GENERAL ELECTIONS - Adrian Faridhi; Sudi Fahmi; Tatang Suprayoga (Jurnal Hukum PRIORIS, 2020)
General Election is a democratic party that involves all citizens to participate in the formation of leaders, but citizen involvement is limited by the electoral mechanism, Law Number 7 of 2017 concerning General Elections regulates the implementation of the 2019 elections, regulations governing the provision of ballots only 2 (two) % of Permanent Voter List (DPT) for each polling station. However, the large voter participation resulted in a shortage of ballots during the election. The research methodology used is in the form of sociological juridical research in this research area in Riau Province using primary data. The results of this study include: there is a shortage of ballots, due to the large number of voters participating in the election, but not registered in the DPT or DPTb, many voters who come only use electronic ID cards or other identities, these voters who have a shortage of ballots and cannot vote , and a solution that addresses the problem of increasing socialization so that voters participate in the election so that they do not lose their right to vote.